Digital Innovations in MSMEs during Economic Disruptions: Experiences and Challenges of Young Entrepreneurs - Lavinia Javier Cueto; April Faith Deleon Frisnedi; Reynaldo Baculio Collera; Kenneth Ian Talosig Batac; Casper Boongaling Agaton (Administrative Sciences, 2022)
The spike in COVID-19 cases all over the world poses a massive impact on various sectors of society. The global economy is no exception, for it has been severely affected by the unprecedented public health crisis leading businesspeople to shutdown commercial establishments and dramatically shifting businesses into digital platforms. Immense challenges brought by the pandemic have turned into great opportunities among entrepreneurs from different parts of the globe. In pursuit of the recovery path, they considered digital tools to be instrumental to surviving the crisis and even thriving in the long term. This study explores drivers and barriers to digital innovations in micro, small, and medium enterprises (MSMEs) during economic disruptions from the perspective of Filipino young entrepreneurs. Researchers employed a qualitative method for the conduct of in-depth interviews with 46 online entrepreneurs in the Philippines and transcribed them for Inductive Content Analysis to generate themes. Results found the adverse effects of the pandemic, which reinforce entrepreneurial innovations of shifting businesses to digital platforms, categorized into intrinsic (e.g., personal and professional growth) and extrinsic (e.g., mobility restrictions, market conditions, and household economic status) motivations. Participants described the barriers to digital entrepreneurship, including skills needed for doing online business, market-related problems in digital platforms, availability of quality internet infrastructures, and the pandemic restrictions. The findings of this study contribute to the entrepreneurship literature and areas for an empirical investigation to develop programs that support entrepreneurs during economic disruptions. This would serve as a guidepost in the formulation of government policies and strategies for economic recovery through digital entrepreneurship while considering the perspectives of young entrepreneurs. This further recommends future related researches to empower entrepreneurs, particularly those in the developing economies during the pandemic and beyond.